Distant Ocular Manifestations after New Coronavirus Infection - U. S. Plyaskina; M. A. Frolov; A. M. Frolov (Oftalʹmologiâ)
Purpose. Theoretically substantiate and practically identify ocular manifestations after the transferred SARS-CoV-2 virus.Patients and methods. For the study we were invited patients who had recovered from SARS-CoV-2 at the hospital of V.M. Buyanova, the age from 20 to 65 years old in period from 2020 to 2021. The total number of patients was 68 people. The patients had with them the results of PCR tests or ELISA tests, or an extract from the hospital confirmed COVID-19 case and also a clinical blood test and CT scan of the chest organs for the period of illness. Before the start of the study, the patients were asked to fill out a questionnaire “Questionnaire for patients who have had a new coronavirus infection” (Appendix 1). For a detailed study of this group of people, each underwent visometry, pneumotonometry, B-scan, a slit lamp study and also a slit lamp study with a 60D lens using 0.5 % Mydriacyl eye drops in the absence of contraindications and pupillography.Results. As a result of the work carried out, we concluded that the virus is capable of causing inflammation of the choroid of the eyeball, uveitis. Moreover, in our study, we identified patients with acquired intermittent divergent strabismus, anisocoria, ptosis, and accommodation disorder. And, in this regard, we came to the conclusion that the coronavirus belongs to the group of neurotropic, as it is able to affect the nervous tissue and cause the above clinical picture. In other words, the virus negatively affects the somatic and autonomic innervation of the oculomotor nerve. As a result of these lesions, we get the corresponding tetrad of symptoms: heterotropy, mydriasis, ptosis, accommodation paralysis.Conclusions. One of the extraordinary complications of coronavirus infection is damage effect to the fibers of the oculomotor nerve, the signs include: strabismus, mydriasis, ptosis and accommodation paralysis. Thus, this clinical picture is associated with the affinity of the virus to the nervous tissue. And as a result, this ability of the virus can probably infect various areas of the brain, which will lead to corresponding complications, not only from the oculomotor nerve, but also from other cranial nerves with the manifestation of the corresponding symptoms, which in theory can aggravate the patient’s condition , causing deep disturbances of motor and sensory innervation.